Eight ways to get a grip on validity as a social imperative - Marceau, Mélanie; Young, Meredith; Gallagher, Frances; St-Onge, Christina (Canadian Medical Education Journal, 2024)
Validity as a social imperative foregrounds the social consequences of assessment and highlights the importance of building quality into the assessment development and monitoring processes. Validity as a social imperative is informed by current assessment trends such as programmatic-, longitudinal-, and rater-based assessment, and is one of the conceptualizations of validity currently at play in the Health Professions Education (HPE) literature. This Black Ice is intended to help readers to get a grip on how to embed principles of validity as a social imperative in the development and quality monitoring of an assessment. This piece draws on a program of work investigating validity as a social imperative, key HPE literature, and data generated through stakeholder interviews. We describe eight ways to implement validation practices that align with validity as a social imperative.